Primeira infância, afrodescendência e e educação no Arraial do Retiro - Damião, Flávia de Jesus (2007)
Childhood’s existence is experienced in a space which lies at the core of a temporal dynamics. The pulsation of that space is marked by the multiple, complex, and irregular potency of experiences and conceptions, both individual and collective, of each person along a timeline. Inserted in the perspective of the culture of African and Afro-Brazilian matrix, the present study aims at investigating how and which experiences are produced and shared by a group of Afro-descendant children from the Arraial do Retiro, a neighborhood in Salvador, trying to identify educational experiences that have been configured in that territory. The present study follows the qualitative approach of the Sociological History, which sets up Afro-descent and the geographical space that has been built historically as the main theoretical-methodological referentials. Adopting a perspective from inside, the streets of that neighborhood, where Afro-descendants constitute a numerical majority, were established as the social space where the research was carried out with a group of nine children, aged between three and nine. During the six meetings with the children of the group, multiple languages have been used: orality, storytelling, drawings, photographs, dynamic classroom-like methods, field notebooks, observation and togetherness, in order to reach the proposed aims. The comprehensive qualitative material that was collected was organized in two levels: 1) general panorama of the first childhood in the neighborhood; 2) and a thorough report of the group of children who took part of the research more intensely. The analysis of the first level has allowed us to identify that there is a diversity of forms of living the first childhood in Arraial do Retiro. Concerning the second level, we proceeded the configuration of the spatial context and the actions of the Afro-descendant children. Thus, it was observed that those children take part of the community’s dynamics of Arraial do Retiro by producing, exchanging, accessing, and spreading social, cultural, and affectionate educational experiences, all of them being born from the relations between youngsters, adults and elderly people in that territory. Judging by the results and the linking between theory and empiricism, I affirm the importance of considering the singularities of the Brazilian and Soteropolitan childhood. I also claim that those specificities are made from the connection between the ethnic, territorial, social, age and gender-oriented senses of belonging, amidst an interpenetration of the collective dimensions.